The cloning of notch1 and groove in Notophthalmus viridescens, the red-spotted newt, and an examination of the expression profiles of both genes in the regenerating forelimb through real time RT-PCR - Sy, Candice (University of Ottawa (Canada), 2003)
Limb regeneration in urodeles is a complex process that involves the reinduction of a number of genes that are expressed during limb development. Notch is an essential developmental gene that is likely to play a pivotal role in the genetic control of forelimb regeneration in the red-spotted newt, Notophthalmus viridescens. In this thesis, a partial cDNA of the newt homologue of notch1 was cloned, as well as a complete cDNA containing only 5 EGF repeats and a NIDO domain which also showed homology to notch1. This truncated version of notch1 is suspected, based on its functional domains, to act as a secreted dominant negative regulator of Notch signaling. Real time RT-PCR detection of expression of both genes revealed that notch is expressed at relatively high levels in both the 24 hour and the 2 week regenerate. This may point towards a functional role for Notch signaling in the wound healing process, through activation of cell migration and mobilization, and in the regeneration blastema, through induction of cell proliferation and repression of differentiation. The truncated notch isoform is expressed at low levels in all the tissues that express notch, but whether this results in dominant negative regulation of Notch signaling is currently unknown. Together, these data point towards a functional role for notch in epimorphic limb regeneration.
Keywords: Biology, Genetics.